REVOLUSJPERADABAN: Dan Implikasinya pada Perkembangan Desain Bagi an Pertama - ( 1) - Djoko Sutjipto (Jurnal Dimensi Seni Rupa dan Desain, 2003)
Abstract ·The first revo/u11on of mankmd civiltza11on was happened when primitive peoplechanged thetr way of lt(e from hunting wtld ammal to be a sheperd. The way of ltving has tomove from one place to another followmg the season. So the criteria of s'1elter must flexibleand could be easy to demoltsh and mstallmg agam. 1ust say like a tend Thi? second revolu11onwent on smce they able to seedmg cereals On this way of living. they have to settle In a fixed area. So that the history of arch/lecture development begm to be pineered